Impact of Birawa Champion Training on the Performance of Housekeeping Employees PT.Telkom Property Makassar - I Kadek Dwi Astika; Muhammad Nur Abdi (PT FORMOSA CENDEKIA GLOBAL, 2023)
PT. Telkom Property's Birawa Champion training is organized internally by the company to form soft skills, increase employee knowledge or knowledge of their respective fields of work, namely Housekeeping, Mechanical Electrics, Security, and Drivers. The organization of Birawa Champion training can also produce superior employees and is expected to be an example or leader in their respective work locations. The purpose of the study was to determine what and how the impact of Birawa Champion training on the performance of housekeeping employees of PT. Telkom Property Makassar. The research method used is a qualitative method using interview and observation techniques. Interviews were conducted focusing on 5 core informants who had attended Birawa champion training. There are 6 questions related to knowledge, soft skills, employee performance, discipline, ethics, and tenant satisfaction. Research on Birawa Champion Training has had a positive impact on the performance of employees who participated in the training, especially in the Housekeeping division, including increased knowledge of their work, increased discipline, as well as employee ethics, and increased employee soft skills so that they are able to become employees who have a leadership spirit at work. Training also improves the quality of employees to be better so that they are able to provide excellent service to customers or tenants, so that indirectly this training also affects tenant satisfaction. This is in accordance with the vision of PT. Telkom Property, which is to become the most preferred technology-based property company in Indonesia